CD44v3, 8‐10 is essential for Slug‐dependent vimentin gene expression to acquire TGF‐β1‐induced tumor cell motility. Issue 8 (8th June 2022) - Qiu, Shichao; Iimori, Makoto; Edahiro, Keitaro; Fujimoto, Yoshiaki; Matsuoka, Kazuaki; Oki, Eiji; Maehara, Yoshihiko; Mori, Masaki; Kitao, Hiroyuki
Abstract: CD44 is a widely expressed polymorphic adhesion molecule that has pleiotropic functions in development and tumor progression. Its mRNA undergoes alternative splicing to generate multiple variant (CD44v) isoforms, although the function of each CD44v isoform is not fully elucidated. Here, we show that CD44v plays an important role in the induction of vimentin expression upon transforming growth factor‐β1 (TGF‐β1)‐induced epithelial–mesenchymal transition (EMT). Among multiple CD44v isoforms expressed in NUGC3 gastric cancer cells, CD44v8‐10 and CD44v3, 8‐10 are involved in the acquisition of migratory and invasive properties associated with TGF‐β1‐induced EMT, and only CD44v3, 8‐10 induces the transcription of vimentin mediated by the EMT transcription factor Slug. In primary tumor specimens obtained from patients with gastric cancer, CD44‐containing variant exon 9 (CD44v9) expression and EMT features [E‐cadherin(−)vimentin(+)] were significantly correlated, and EMT features in the cells expressing CD44v9 were associated with tumor invasion depth, lymph node metastasis, and pStage, which indicate invasive and metastatic properties, and poor prognosis. These results indicate that certain CD44v isoforms promote tumor cell motility and metastasis in gastric cancer in association with EMT features, and CD44v3, 8‐10 may contribute to these clinical characteristics. Abstract : In this study, we show that CD44v3, 8‐10 and CD44v8‐10 are involved in the acquisition of migratory and invasive properties associated with TGF‐β1‐induced EMT, and only CD44v3, 8‐10 induces the transcription of vimentin mediated by the EMT transcription factor Slug. Clinically, tumors with the combination of CD44v9 expression and EMT features were significantly associated with tumor invasive and metastatic activities. Therefore, targeting CD44v may be a promising therapeutic strategy to prevent tumor progression at the early stage of gastric cancer.